Determination of Optimal Cylinder Gas Packaging Distribution Routes Through the Solution of the Capacitated Vehicle Routing Problem at PT Samator Gas Industri Balikpapan - Surianto, Vincent; Wahyuda, Wahyuda; Sitania, Farida Djumiati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2026)
The distribution of industrial and medical gases in Indonesia faces significant supply chain challenges. In general, the distribution is not yet fully adequate to meet the continuously growing demand. Based on this industrial issues, the researcher conducted an observation of PT Samator Gas Industri Balikpapan distribution activities. The company has not maximized the truck load by only loading 60 to 80 cylinders per truck. The issue has resulted in fuel costs not being optimal. Another issue arises because the distribution routes is done subjectively without considering the best route to deliver products. In this research, the issue was addressed by solving the Capacitated Vehicle Routing Problem (CVRP) using the Clarke-Wright Saving Heuristic Algorithm and the Sweep Algoritm (cluster first, route second), combined with the Nearest Neighbor route sorting method. Based on the research results, the Clarke-Wright Saving Heuristic Algorithm successfully reduced the travel distance to 167.1 km and resulted in fuel cost savings of IDR402,051.67 (49.21%). Meanwhile, the route generated by the Sweep Algorithm also showed better results compared to the initial route. The Sweep Algorithm produced savings of IDR340,465.00 (41.67%). Although the results obtained were not better than those of the Clarke-Wright Saving Heuristic Algorithm, the Sweep Algorithm has the advantage of simplifying the grouping process of delivery points based on their geographical proximity, making the route more efficient even without complex calculation steps.